Risk of malignant progression in Barrett's esophagus indefinite for dysplasia - Ma, M. (Dis Esophagus, 2016)
Barrett's esophagus is a well-recognized risk factor for esophageal adenocarcinoma. The natural history of Barrett's esophagus classified as ‘indefinite for dysplasia’ (IND) is poorly characterized. The aim of this study is to characterize the natural history of IND by determining the rate of neoplastic progression and identifying risk factors for progression. Patients from the University of Pennsylvania Health System pathology database and Barrett's esophagus registry with a diagnosis of IND between 2000 and 2014 were identified. Exclusion criteria included: (1) prior diagnosis of low-grade dysplasia (LGD), high-grade dysplasia (HGD), or esophageal adenocarcinoma (EAC); (2) presence of LGD, HGD, or EAC at the time of diagnosis of IND; and (3) lack of follow-up endoscopy after diagnosis. Patients with neoplastic progression were classified as having either prevalent disease (LGD, HGD, or EAC on surveillance biopsy within 12 months of IND diagnosis) or incident disease (LGD, HGD, or EAC on surveillance biopsy >12 months after IND diagnosis). One hundred six patients were eligible for analysis. Of 87 patients with follow-up endoscopy and biopsies within 1 year of IND diagnosis, 7 (8%) had prevalent disease (2 LGD, 4 HGD, 1 EAC). The prevalence of LGD was 2.3%, HGD was 4.6%, and EAC was 1.1%. Importantly, four of the seven prevalent (2 LGD, 2 HGD) cases were found to have dysplasia within 6 months of IND diagnosis. No demographic or endoscopic characteristics studied were associated with prevalent disease. Of the 106 IND patients, there were 66 patients without prevalent dysplasia with >1-year follow-up. Three (4.5%) progressed (1 to LGD after 12 months, 2 to HGD after 16.5 and 28 months), yielding an incidence rate for any dysplasia of 1.4 cases/100 person-years and HGD/EAC of 0.9/100 person-years. Risk factors for incident disease were smoking (p = 0.02) and Barrett's esophagus segment length (p = 0.03). IND is associated with considerable risk of prevalent dysplasia, especially within the first 6 months after diagnosis. However, the incidence of HGD/EAC is low and similar to previous studies of IND. These data suggest that IND patients should have repeat endoscopy within 6 months with careful surveillance protocols. Longer BE length and smoking history may help predict which patients are more likely to develop dysplasia, and therefore identify patients who may warrant even closer monitoring.